2020
DOI: 10.1182/blood.2020005288
|View full text |Cite
|
Sign up to set email alerts
|

Daratumumab, lenalidomide, bortezomib, and dexamethasone for transplant-eligible newly diagnosed multiple myeloma: the GRIFFIN trial

Abstract: Lenalidomide, bortezomib, and dexamethasone (RVd) followed by autologous stem cell transplantation (ASCT) is standard frontline therapy for transplant-eligible patients with newly diagnosed multiple myeloma (NDMM). This study evaluated addition of daratumumab (D) to RVd in ASCT-eligible NDMM patients. Patients (N=207) were randomized 1:1 to receive RVd ±D induction (4 cycles), ASCT, RVd ±D consolidation (2 cycles), and lenalidomide ±D maintenance (26 cycles). At the primary endpoint analysis, the stringent com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
481
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 524 publications
(563 citation statements)
references
References 37 publications
15
481
1
3
Order By: Relevance
“…GRIFFIN is another important phase II trial evaluating the efficacy and safety of the addition of daratumumab to the combination of bortezomib, lenalidomide and dexamethasone (Dara-VRd) in NDMM TE patients [27]. With a median follow-up of 22.1 months, the rate of sCR was 62.2% in the daratumumab arm vs. 45.4% in the control arm, with a 24-month PFS of 95.8% vs. 89.8%, respectively.…”
Section: Naked Monoclonal Antibodiesmentioning
confidence: 99%
“…GRIFFIN is another important phase II trial evaluating the efficacy and safety of the addition of daratumumab to the combination of bortezomib, lenalidomide and dexamethasone (Dara-VRd) in NDMM TE patients [27]. With a median follow-up of 22.1 months, the rate of sCR was 62.2% in the daratumumab arm vs. 45.4% in the control arm, with a 24-month PFS of 95.8% vs. 89.8%, respectively.…”
Section: Naked Monoclonal Antibodiesmentioning
confidence: 99%
“…Responses have continued to deepen throughout maintenance-rates of sCR improved for D-RVd versus RVd (62.6% vs 45.4%; p=0.0177), as did rates of MRD negativity at the 10 −5 threshold (51.0% vs 20.4%; p<0.0001). 36 Overall, the regimen with dara (D-VRd) was found to be safe and more effective than VRd alone, with an increase in any-grade infection rates of 91% vs 62%, largely due to grade 1/2 upper respiratory tract infections. Stem cell yield was adequate in both arms.…”
Section: Frontline Daratumumab Transplant-eligible Patientsmentioning
confidence: 94%
“…Among patients with keratopathy worse than baseline at the end of treatment, the events resolved in 9 (36%) of 25 patients in the 2.5 mg/kg cohort, with a median time to resolution of 71 days (interquartile range (IQR) 57-99), and 8 (28%) of 29 patients in the 3.4 mg/kg cohort, with a median time to resolution of 96 days . No benefit was observed for prophylactic steroid eyedrop administration, as median time to keratopathy was similar between eyes treated prophylactically with corticosteroid eye drops and without (24 (IQR 21-30) and 27 days, respectively in the 2.5 mg/kg cohort and 25 (9-40) and 25 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) days, respectively in the 3.4 mg/kg cohort). 203 Panel recommendations ► Prior to receiving belantamab mafodotin the patient should receive a complete ophthalmological examination.…”
Section: Administration Dosing and Monitoringmentioning
confidence: 96%
“…Results showed an improvement in the overall response rate, stringent complete response rate, and rate of minimal residual disease negativity (median progression free survival, not reached). 53 A randomized phase III trial has shown that subcutaneous daratumumab was noninferior to intravenous daratumumab in terms of efficacy and pharmacokinetics, and had an improved safety profile in relapsed and refractory multiple myeloma leading to its recent FDA approval in 2020 (median progression free survival 5.6 v 6.1 months). 54 Although elotuzumab has limited activity on its own, 63 it has shown significantly improved over all response rates and progression free survival when combined with immunomodulatory drugs lenalidomide in a randomized phase III trial (median progression free survival 19.4 v 14.9 months) 55 56 64 and pomalidomide in a randomized phase II trial (10.3 v 4.7 months).…”
Section: Median Progression Free Survival (Months)mentioning
confidence: 99%